GASIFICATION KINETICS OF ULTRAFINE COAL CHAR OXIDATION IN FLAME REACTIONS - John, G. R.; Mkilaha, I. S.N. (Tanzania Journal of Engineering and Technology, 2018)
GASIFICATION KINETICS OF ULTRAFINE COAL CHAR OXIDATION IN FLAME REACTIONS